Post‐democracy: From the depoliticisation of citizens to the political automata of perpetual war. Issue 3 (December 2015) - Mendieta, Eduardo
Abstract : Eduardo Mendieta argues that 'post‐democracy' has been misapplied to diagnose a failure of democracy, where democracy instead remains unfinished. We are not living in an age of post‐democracy, he argues, but in an age of 'not enough democracy', or 'democracy to come'.